2013
DOI: 10.1111/ced.12164
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated human melanocytes express and release interleukin-8, which is inhibited by luteolin: relevance to early vitiligo

Abstract: Summary Vitiligo is a disorder of depigmentation, for which the pathogenesis is as yet unclear. Interleukin (IL)-8 is a key inflammatory chemokine. We investigated the regulation of IL-8 production in human melanocytes, and the IL-8 serum levels and skin gene expression in patients with vitiligo and in controls. Cultured melanocytes were stimulated for 24 h with tumour necrosis factor (TNF) 100 ng/mL and IL-1β 10 ng/mL, with or without pretreatment with luteolin 50 μmol/L for 30 min, and IL-8 release was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 9 publications
2
22
1
1
Order By: Relevance
“…15 Luteolin has been demonstrated to be a potent antiinflammatory agent. 16,17 However, little is known about its effect on P. acnes-induced inflammatory reactions. To prove A control experiment without P. acnes treatment was conducted in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…15 Luteolin has been demonstrated to be a potent antiinflammatory agent. 16,17 However, little is known about its effect on P. acnes-induced inflammatory reactions. To prove A control experiment without P. acnes treatment was conducted in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine is involved in the acute inflammatory response in vivo and exhibits a chemotactic activity for neutrophils, T cells, fibroblasts, endothelial cells and melanocytes in vitro . Miniati et al observed increased release of CXCL8 from human melanocytes in response to TNF‐α and IL‐1β, and elevated CXCL8 gene expression in the lesional skin of patients with new‐onset and active vitiligo. Moreover, CXCL8 has been reported to induce oxidative stress, leading indirectly to both keratinocyte and melanocyte apoptosis in vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…They have the capacity to phagocytosis and are capable of antigen processing and presentation . In response to various stimuli, melanocytes can produce and release soluble mediators of inflammation, such as nitric oxide, interleukin (IL)‐1α, IL‐1β, IL‐6, IL‐8, tumor necrosis factor (TNF)‐α and interferon (INF)‐β, which could affect melanocytes themselves or/and other cells of the epidermis, contributing to a local immune response. Melanocytes also produce several immunosuppressive molecules, including proopiomelanocortin‐derived adrenocorticotropic hormone and α‐melanocyte‐stimulating hormone, corticotropin‐releasing hormone, cortisol, corticosterone and other steroids …”
Section: Introductionmentioning
confidence: 99%
“…This results in increased production of IL‐6 and IL‐8 by melanocytes . Increased IL‐8 expression was likewise found in skin of patients with active disease . Overproduction of pro‐inflammatory cytokines and decreased availability of immunosuppressive regulatory T cells, combined with increased abundance of cytotoxic T cells, all contribute to depigmentation.…”
Section: Autoimmune Pathogenesis Of Vitiligomentioning
confidence: 99%